A Thick Film Sensing Element for True RMS Meter - Marko Hrovat; Miran Zgonik; Darko Belavic (Active and Passive Electronic Components)
A sensing element for true RMS meter was realized in thick film technology. The temperature gradient along a substrate was measured by thick film thermocouples, based on a combination of Pt/Ag-Pd/Ag, Pt/Au-Au and Ni-Cr. A voltage response of the element was measured as a function of the current through the heating resistor at different ambient temperatures. The transfer function K(T) of the RMS meter was found to be relatively independent of ambient temperature, which means that the voltage response is usably linear.